2016
DOI: 10.1007/s12035-016-0307-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice

Abstract: Sepsis survivors frequently develop late cognitive impairment. Because little is known on the mechanisms of post-septic memory deficits, there are no current effective approaches to prevent or treat such symptoms. Here, we subjected mice to severe sepsis induced by cecal ligation and puncture (CLP) and evaluated the sepsis-surviving animals in the open field, novel object recognition (NOR), and step-down inhibitory avoidance (IA) task at different times after surgery. Post-septic mice (30 days post-surgery) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…() and Talbot and Wang (). Similar recent studies into the cognitive impairment in a post‐sepsis mouse model (Neves et al ., ) showed the same detailed IR pathophysiology, including changes surrounding IRS‐1 and Akt, as well as a positive response to a glucagon‐like protein‐1 mimetic that reverses IR, as reported in AD in this study. In particular, infliximab completely blocks the Aβ‐induced inhibition of IRS‐1, the insulin receptor component discussed below in a tau context (Bomfim et al ., ).…”
Section: Insulin Resistancementioning
confidence: 97%
“…() and Talbot and Wang (). Similar recent studies into the cognitive impairment in a post‐sepsis mouse model (Neves et al ., ) showed the same detailed IR pathophysiology, including changes surrounding IRS‐1 and Akt, as well as a positive response to a glucagon‐like protein‐1 mimetic that reverses IR, as reported in AD in this study. In particular, infliximab completely blocks the Aβ‐induced inhibition of IRS‐1, the insulin receptor component discussed below in a tau context (Bomfim et al ., ).…”
Section: Insulin Resistancementioning
confidence: 97%
“…Although preliminary, these early studies point out to GD as an important factor influencing offspring brain health. Moreover, studies from our group and others have recently described how inflammation and disrupted insulin signaling in memory-related brain regions occur in conditions that affect cognition (Bomfim et al 2012, Lourenço et al 2013, Neves et al 2016. Therefore, we also focus on the evidence suggesting that downregulation of insulin receptors and its intracellular cascade are seen in the brains of GD offspring and could contribute to affect their behavior.…”
Section: Introductionmentioning
confidence: 95%
“…These patients often present late cognitive impairment and some of them never fully recover (Iwashyna et al 2010, Pandharipande et al 2013, Semmler et al 2012. Using an experimental model of sepsis, we were able to mimic the late cognitive impairment seen in patients and found that increased hippocampal expression of TNF-α and impaired insulin signaling in this brain region also accompany sepsis-associated late cognitive decline (Neves et al 2016). Whether impaired brain insulin signaling is a common denominator of other conditions affecting memory remains to be established.…”
Section: Metabolic and Behavioral Consequences Of Brain Insulin Signamentioning
confidence: 99%
“…Increased expression of miR-200b or -c diminishes secretion of the Aβ oligomers and, consequently, reduces IRS-1 phosphorylation in serine residues, which is associated with cognitive impairment and memory loss in AD [ 142 , 143 , 144 ]. Exacerbated IRS-1 phosphorylation on serine residues may also induce dephosphorylation of protein kinase B (AKT) by inhibiting pro-survival signaling pathways and activation of glycogen synthase kinase-3β (GSK-3β), a cellular pathway that leads to neuronal apoptosis [ 145 ]. GSK-3β, in turn, inhibits the induction of the autophagosome to the lysosome and stimulates the insertion of the autophagosome to the multivesicular body (MVB).…”
Section: Mirnas and Ad Pathophysiologymentioning
confidence: 99%